Prevalence and molecular characterization of Cryptosporidium spp. in dairy cattle in South Bohemia, the Czech Republic - Ondráčková, Zuzana (Jihočeská univerzita, 2009)
The prevalence and molecular characterization of Cryptosporidium spp. in slaughtered cattle 6 months and older was performed. Three species of Cryptosporidium were identified. A subtype of C. parvum was obtained.
Prevalence and molecular characterization of Cryptosporidium spp. in dairy cattle in South Bohemia, the Czech Republic
Keywords: Cryptosporidium spp.; cattle; genotyping; SSU; GP60; slaughterhouses; Cryptosporidium spp.; cattle; genotyping; SSU; GP60; slaughterhouses